A novel polysaccharide-based bioflocculant produced by Bacillus subtilis 35A and its application in the treatment of dye decolorization, heavy metal ion adsorption and meat product wastewater - Dai, Jinping; Zhao, Xingxiu; Mu, Shengdong; Yang, Qinghuan; Zhao, Changqing; Zhao, Zhifeng (Frontiers in Microbiology, 2024)
Optimizing the fermentation process of microorganisms with exceptional bioflocculant-producing capabilities is crucial for the production of bioflocculants. The application of bioflocculants to various pollutants highlights their significant advantages in water treatment. Therefore, the culture conditions of Bacillus subtilis 35A with exceptional bioflocculant-producing capabilities were optimized. The bioflocculant (MBF) was obtained by alcohol percipitation from the fermentation supernatant, and its physicochemical properties were analyzed to explore its application in the treatment of dyes, heavy metal ions, and organic wastewater. The results indicate that, using cyclodextrin and yeast extract as carbon and nitrogen sources, after 48 h of fermentation at the initial pH, the bioflocculant (MBF-35A) yielded 10.47 g/L with a flocculation rate of 96.57% for kaolin suspension. The chemical analysis demonstrated that MBF-35A is mainly composed of polysaccharide (81.74%) and protein (16.42%). FITR and XPS analysis indicated that MBF-35A mainly contains major elements such as carbon, nitrogen, and oxygen, with functional groups (-OH, C-O, C-H, and C-O-C) that are beneficial for flocculation. MBF-35A exhibited a dye decolorization efficiency exceeding 95% and removed 41.05 and 48.93% of Cr6+ and Cu2+ ions, respectively. In meat wastewater treatment, the effective removal rates of ammonia nitrogen (26.87%), COD (51.16%), total nitrogen (37.76%), and total phosphorus (55.81%) highlight its potential in organic waste treatment. In brief, not only does MBF-35A exhibit efficient production and excellent flocculation performance as a bioflocculant, but it also shows significant biological and environmental benefits in dye, heavy metal ions, and organic wastewater treatment.